STRATEGI PENGAWAS DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI MADRASAH IBTIDAIYAH NEGERI BUNGCALA KABUPATEN ACEH BESAR - Rachmayani .; Murniati AR; Nasir . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
Supervisor is a profession, therefore it is expected that supervisors can provide guidance to teachers in improving teacher pedagogic competence. The supervisory strategy greatly influences the teacher's pedagogical competence, which is done by coaching and providing opportunities for teachers to improve their competence. Thus, supervisors in Madrasah Ibtidaiyah are expected to 1) increase the competence of teachers, 2) know the strategies used by the supervisor, 3) know the supervisor strategy in evaluating the teacher's success in developing the learning, and 4) to know the obstacles faced by the supervisor. The approach used is descriptive qualitative approach, with observation data collection techniques, interviews and documentation studies, with the object of research is the supervisor. From the research results can be concluded that the strategies used by supervisors in improving the competence of teachers in Madrasah Ibtidaiyah Negeri Bungcala by doing KKG activities, Training, Scientific activities, seminars and Tem teaching.Keywords: strategy, superintendents, pedagogical competence and teacher